Survey the effect of simultaneous implementation of ergonomic interventions and management decisions on reduction of musculoskeletal disorders and improvement of work postures in the milking worker of dairy plant - Azim Karimi; Behzad Mahaki; Mohammad Hossein Ebrahimi; Mohammad Taghi Bastami; Amin Babaei Pouya; Farzaneh Kasraei; Abdullah Barkhordari (Salāmat-i kār-i Īrān, 2020)
Background and aims: Work-related musculoskeletal disorders usually engage the lower back, cervical spine and upper extremities (shoulder, elbow, wrists, hands and fingers). According to reports from around the world, work- related musculoskeletal disorders are the most common occupational disorders and diseases. There is no accurate estimate of the prevalence of these disorders in Iran, but studies have reported a high prevalence. These disorders are the most important cause of absenteeism among workers. They also play a significant role in the premature disablement of workers. Disorders also induce economic losses in human societies due to the loss of working days, the cost of treatment and rehabilitation, reduction of quality of life of affected people and their families.  These disorders affect the individual, organization, and society. Studies have shown that musculoskeletal disorders are very costly, in such a way that they induce the highest suffering for the patient and among them, back pain has the highest rank. Many of these disorders are due to the failure to observe the ergonomic principles and the unfavorable and non-standard conditions governing the work environment and how to perform the job.  It can be clearly stated that the range of ergonomic problems in work environments is not limited to musculoskeletal injuries, but also include loss of productivity and efficiency, increased errors, fatigue, discomfort and environmental stress.  The risk factors for these disorders are multifactorial, and they are still not fully understood in some respects. The most important factors include occupational ones such as unfavorable work environment, manual work, heavy lifting, repetitive and heavy work. Agriculture, like mining and construction, is recognized as one of the three highly hazardous and high-risk industries in terms of health. National and international studies show that the physical needs of farming occupation can be a cause of work-related musculoskeletal disorders. Dairy plants is one of the subsectors of the agriculture and food. Dairy plants, and especially milking the cows, affects the musculoskeletal system of the workers in the industry due to physical needs, poor working posture and repetitive movements and tasks. Musculoskeletal disorders in the areas of waist, shoulders, hands, wrists and knees are one of the common problems in this industry. Cow-milking is one of the most hazardous sectors in terms of ergonomic risk factors in the livestock industry. According to studies, about one-third of workers in the milking sector often experience symptoms of pain in the shoulders and necks. Increased work time, milking more cows per hour, high physical activity and repetitive tasks are among the potential risk factors for work-related musculoskeletal disorders in this industry. This study aims at investigating the effects of ergonomic engineering interventions and management decisions on reducing the frequency of musculoskeletal disorders and improving work postures among milking workers in dairy plants. Methods: This is an interventional study performed in a dairy plants with 240 personnel working in different parts of Isfahan. In the primary health and safety investigations in this industry, the hazardous milking sector was selected as the research environment because it produces the highest number of physical complaints by personnel, the highest number of occupational accidents and back injuries. All 48 workers of the milking sector were investigated. The purpose of the study and the methodology was fully explained to the participants in the study. They were assured that, firstly, their information would be completely confidential to the researchers. Secondly, participation in this study was entirely voluntary and if they were not willing to participate in the study, there were no consequences for them. After explaining the study, in case they were willing, the consent form was completed by the participants and the presence of the individual was confirmed. The procedure was carried out in 4 steps as follows. 1. Evaluation of the occupation of milking and determining the frequency of disorders among the workers. 2. Implementing intervention programs. 3. Re-evaluation of the occupation of milking and determining the frequency of disorders after completing the intervention program. 4. Comparing the results before and after the interventions. In order to evaluate musculoskeletal disorders, the Persian version of Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) was completed by the participants. The questionnaire analyzes the frequency of discomfort, severity of discomfort and its impact on work power in the last week in twelve parts of the body. The CMDQ is a suitable tool for the evaluation of work-related musculoskeletal disorders. The ergonomic evaluation uses a quick exposure check (QEC) posture analysis method. This methodology allows assessing worker exposure to a wide range of risk factors for musculoskeletal disorders. In this method, part of the work is completed by the observer and the other part by the operator. The QEC methodology is used to assess a range of occupations including: manual handling, repetitive tasks, dynamic tasks, tasks involving sitting and standing. In the QEC posture analysis, psychosocial risk factors are considered in addition to physical risk factors. This method is also an appropriate method for evaluating interventional operations, because immediately and after intervention programs, the impact of interventions can be assessed by re-evaluating the work environment. After the analysis, the results were discussed with the top management of the organization and officials from other sectors to determine intervention measures. At the end of the meeting, decisions were made to improve the ergonomic situation of the milking personnel, which include the engineering interventions, management interventions and implementation of educational programs. The time required for the implementation of the interventions and the authority responsible for their implementation was determined. After completing the intervention, the frequency of musculoskeletal discomfort among the participants and the ergonomic status of the milking occupation were re-evaluated using the CMDQ and QEC posture analysis. In the end, in order to investigate the effect of these interventions on decreasing musculoskeletal discomfort and improving personnel postures, the scores before and after the evaluation compared by use of paired t-test and their significance was examined. Results: All participants in this study were men. 56.26% of the research population was under 30 years old and 66.66% had a work experience of under 4 years of age, indicating the low age and low experience of the population studied. The highest score of the CMDQ in terms of the frequency of discomfort was related to the lower back (364.5 before and 187.5 after intervention), shoulder (190.25 before intervention and 114 after intervention) and neck (164.5% before and 85.5 after intervention), respectively. Paired t-test showed that the scores of the CMDQ were significantly decreased after intervention in the three parts of frequency of discomfort, severity of discomfort, and its impact on work (p-value <0.05). There was no significant difference between the scores of the questionnaire in three areas: upper arms, hips/ buttocks and legs before and after the intervention (p-value> 0.05) but in other areas (neck, shoulder, upper back, lower back , forearm, wrist, thigh, knee and leg) (p-value <0.05). The final score of analysis of the work environment using the QEC posture analysis methodology has significantly decreased after completion of the interventions. Conclusion: The results of this study showed that the prevalence of musculoskeletal disorders, especially in the lower back, neck and shoulders, is high among cow-milking workers, and corrective ergonomic measures are needed to prevent the disorders. Also, a careful examination of the milking occupation showed that the most important risk factors for the milking workers included: awkward postures, static position for long periods of time, high work hours, uniformity of duties due to the nature of the job and failure to observe the principles of occupational ergonomics at the work environment. Therefore, corrective measures to improve the ergonomic status of milking workers should be elimination of the risk factors identified. Findings of this study showed that the implementation of ergonomic training programs included the selection of the best physical condition with the lowest pressure on the body during milking operations, correct and ergonomic principles of manual handling, improving posture and reducing the risk of disorders (decreasing the score of QEC posture analysis). Also, the results of this study showed that the simultaneous implementation of ergonomic engineering interventions, management plans and training programs will result in a reduction in the frequency of work-related musculoskeletal disorders and the improvement of work posture. Considering that milking activity in dairy plants has the same procedures and equipment, corrective measures of this research are also useful for other dairy plants. One of the limitations of this study was that there is no control group and it is recommended that in future studies, taking into account the control group, the roles of each intervention should be separately reported and compared. For example, the role of ergonomic engineering interventions should be compared with training and management plans and the effectiveness of each one in the reduction of disorders is analyzed so that the measures are prioritized according to their impact. This prioritization can help managers who cannot implement all interventions simultaneously to select the most effective actions.